Production of Computational Learning Activities in the Training of the Mathematics Teacher - Fiorezi de Marco, Fabiana (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
This article is the result of a survey conducted in a Federal University of State of Minas Gerais, Brazil, degree course in Mathematics. Emphasizes the importance of the use of computing environments and reports the production of a learning activity designed by future mathematics teachers exploring the concept of area. The written productions, reports of activities and discussions taped interviews comprised the scenario of our anlyzes having as main goal is to analyze the implications that didactic production computational activities education developed by licensees can bring to the training of future teachers of mathematics, having as theoretical perspective the historical-cultural knowledge and Activity Theory points out that computing environments, when carefully planned activities, are educational resources effective for the cons-truction of mathematical knowledge. This research is characterized as an intervention research with interpretive analysis of the information produced. As a result, the analyzes indicate that the protagonists of the research developed a process of reflection on the activity of teaching, conceiving it as a surce of the need and reason for teaching and learning mathematics. In addition, there are some implications that didactic teaching activities intentionally planned and mediated by the teacher, can provide for the training of future teachers.